(untitled) (Daffodil International University Journal of Science and Technology, 2010)
In this study, tribological properties of Hi-HVOF sprayed WC-Cr-Ni cermet coatings were investigated experimentally under lubricated rolling-sliding contact. Coatings were deposited onto the induction hardened carbon steel and carburized hardened steel materials. Substrate surfaces were prepared by axially grinding, blasting and circumferentially grinding. Under the operating conditions of contact pressure PH=1.4 GPa and slip ratio s=-28.0%, the effects of substrate hardness and substrate surface kind on the tribological properties of the cermet coating were examined. It was found that cermet coating showed a long life and durability was not influenced by the substrate hardness and substrate surface kind. It was also found that during the running-in process, oil film formation was hardly influenced by the substrate hardness and substrate surface kind. On the other hand, surface hardness and surface roughness of the coating were more influenced in the case of circumferentially ground substrate than that in the case of axially ground or blasted substrate. In addition, coating material loss was very high in the case of circumferentially ground substrate when the substrate material was induction hardened carbon steel. Keywords: Tribological Properties, WC-Cr-Ni Cermet, Substrate Hardness, Substrate Surface Kind DOI: 10.3329/diujst.v4i1.4356 Daffodil International University Journal of Science and Technology Vol.4(1) 2009 pp.50-56